Numerical Study of Composite Fiberglass Cross Arms under Statics Loading and Improvement with Sleeve Installation - Mohamad D.; Syamsir A.; Beddu S.; Abas A.; Ng F.C.; Razali M.F.; Seman S.A.H.A. (Institute of Physics Publishing, 2023)
Deformation; Manufacture; ACP simulation; ANSYS software; Cross arm; Deformation and stress; Fiberglass composites; Maintenance cost; Structural deformation; Viable solutions; Glass fibers